PENGEMBANGAN MEDIA PEMBELAJARAN PAI BERBASIS CANVA: ANALISIS EFEKTIVITAS TERHADAP LITERASI DIGITAL DAN CAPAIAN PEMBELAJARAN SISWA SMP NEGERI 1 MALO - Maimun; Burhanuddin, Hamam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology requires Islamic Education (PAI) teachers to create innovative and relevant learning media. This study aims to develop Canva-based PAI learning media and test its feasibility and effectiveness in improving students' motivation and learning comprehension. Canva was selected for its ability to provide engaging visual design features, such as infographics, videos, and interactive teaching materials. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects involved junior high school students. Data were collected through validation questionnaires from material and media experts, classroom observations, and student response questionnaires. The data were then analyzed using descriptive quantitative methods. The results indicate that the Canva-based PAI learning media possesses a very high level of feasibility based on expert assessments. Empirically, the use of this media is proven effective in increasing students' motivation, engagement, and conceptual understanding due to its systematic presentation and harmonious visuals. Thus, developing Canva-based media serves as an innovative and practical solution relevant to 21st-century educational demands in enhancing the quality of digital learning. Keywords: Canva, learning media, Islamic Education, educational technology, digital learning.